Kedudukan Harta Bersama dalam Perkawinan Poligami yang Tidak Dicatatkan - Oktafia, Yeni; Sudarsono, Sudarsono (Universitas Negeri Malang, 2021)
This study aimed to analyze the distribution of joint property in unregistered polygamous marriages and the legal certainty of the distribution in unregistered polygamous marriages. This study was normative juridical research because this study used the statutory approach, the conceptual approach, and the historical approach. Data collection techniques were sourced from primary, secondary, and tertiary legal sources. The researcher analyzed data with descriptive analysis and interpretation methods. The study results showed that the distribution of joint property in polygamous marriages that were not registered must carry out isbat marriage so that there was a guarantee of legal protection for the distribution of joint property. The division of joint property in a polygamous marriage that was not registered was equated with a legal marriage as long as it could be proven to have good faith in its implementation. The legal certainty of the distribution of joint assets in unregistered polygamous marriages could be carried out by law chosen by husband and wife by deliberation and consensus. If submitted in court, it was based on the right of rechtsvinding based on ijtihad and the noble values of Indonesian customary law.